2023
DOI: 10.3389/fendo.2023.1107511
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA sequencing reveals in vivo osteoimmunology interactions between the immune and skeletal systems

Abstract: BackgroundWhile osteoimmunology interactions between the immune and skeletal systems are known to play an important role in osteoblast development, differentiation and bone metabolism related disease like osteoporosis, such interactions in either bone microenvironment or peripheral circulation in vivo at the single-cell resolution have not yet been characterized.MethodsWe explored the osteoimmunology communications between immune cells and osteoblastic lineage cells (OBCs) by performing CellphoneDB and CellCha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Disorders in Notch signaling are related to human diseases that affect bones. Wang et al identified JAG1 and NOTCH1 as L-R genes with ossificationrelated functions using single-cell RNA sequencing, which further confirmed the inevitable relationship between the two and osteoporosis (Wang S. et al, 2023). Through animal experiments, Hui et al found that the targeted inhibition of JAG1/ NOTCH1 signal transduction can promote poor osteogenic differentiation of bone marrow mesenchymal stem cells (Han et al, 2022).…”
Section: Discussionmentioning
confidence: 92%
“…Disorders in Notch signaling are related to human diseases that affect bones. Wang et al identified JAG1 and NOTCH1 as L-R genes with ossificationrelated functions using single-cell RNA sequencing, which further confirmed the inevitable relationship between the two and osteoporosis (Wang S. et al, 2023). Through animal experiments, Hui et al found that the targeted inhibition of JAG1/ NOTCH1 signal transduction can promote poor osteogenic differentiation of bone marrow mesenchymal stem cells (Han et al, 2022).…”
Section: Discussionmentioning
confidence: 92%